The subjects of investigation of the teachers: experiences and analysis - García-Cortés, Teresita de Jesús; Ríos Castillo, Alma Carolina (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
About what the teachers of our teacher training institution investigate, is the subject of this work. With a qualitative approach, emerging design methodology and instruments such as Google form, the analysis of the thesis documents of the 2020-2022 generation, we present the answer to this question. The Maestrantes faced the atypical situation of the pandemic and confinement due to covid-19 and carried out their theses under the research-action methodology. They developed competencies of the Institution’s graduate profile, by generating knowledge and improving the quality of their teaching for the benefit of their students.